Epístolas profanas: performances dos silêncios manifestos - Gomes, Morgana Barbosa (2019)
The Profane Epistles are cartographies (Suely Rolnik, Roberta Romagnoli) drawn from some pulsations that move us, namely: an expression of silence through artistic performances in the streets; an aesthetic performances (Susan Sontag) built at the intersection among art, philosophy and contemporary anthropology; a performance investigation (Ciane Fernandes, Brad Haseman) whose method implicates the epistolary literature as a genre of knowledge. We started from the cultural silencing of women, interacting with some thinkers, like Djamila Ribeiro, Sulei Carneiro, Marcia Tiburi, Gloria Anzaldúa, Grada Kilomba, Chimamanda Adichie, Gayatri Spivak, Judith Butlher, Simone de Beauvoir, Michelle Perrot, form among others, to demonstrations of this silence through artistic and cultural performances (Eni Orlandi, Richard Schechner, Paul Zumthor). This espistolary cartography is a composition of letters exchanged with readers, artists, professors, students, reseachers, witnesses, classmates and friends, from among other real and fictitious addressees, like cities and personified entities, artistic and highly – regarded characters, interacting with references who form the body of work. The letters refer to emergent questions from our practical experiences from the artistic programs Aesthetic of Silence (BA, 2015) and Poetics of Silence (GO, 2019), to the artistic performances Poems & Whispers, Profane Epistles, Elephant Woman, Silence Constellation, Beauty of Silence, Lady of Silence, which we performed in the streets of some brazilian cities amongst Bahia, Brasília e Goiás (2015-2019). We refered to writers who expressed their silence in the literature (Cora Coralina, Clarice Lispector, Hilda Hislt, Lya Luft, Virgínia Woolf, Franz Kafka), from among artists of other languages, writing to brazilian researchers contemporary with the silence in the arts. In this performative research, we experienced a synthesis between subject and object, theory and practice, content and shape, method and criation, being able to contribute to epistemologies and methodologies of researches into arts, interdisciplinary approaches to Cultural Performances.